MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs